(untitled) (Fiep Bulletin - online, 2013)
The aim of this study was to determine the indicators of obesity of schoolchildren aged 9 to 14 years old in the city of Arapiraca/Alagoas. This study has a cross-sectional descriptive and quantitative approach with a sample of 3918 students enrolled in 10 schools in the urban area of ??the city of Arapiraca. We collected the amounts related to subscapular skinfold, triceps, height, total body mass, hip circumference, and subsequently calculated the percentage of fat (% BF) using the protocol of Lohman (1992), by BMI classification proposed by Cole et.al. (2000), and IAC through the classification proposed by Bergman et al. (2011). We used the statistical central tendency. As for the mean values ??of relative body fat results were classified, mostly in both boys and girls, as moderately high. Regarding BMI, the average scores were classified mostly as normal for both sexes. Finally, the average values ??of the IAC for males, most were classified as overweight, while for females in all age groups analyzed were classified as normal. The study concludes that there is a difference between the proposed classifications of relative body fat (% BF), BMI and IAC, showing that it is essential to conduct further studies that can verify the existence of correlation between the variables.